From colony to SAR: advocacy planning in the executive-led polity of Hong Kong - Chui, Ernest W.T.; Kam, Ng Mee (1998)
In 1997, Hong Kong underwent a momentus transfer of sovereignty. The new SAR government inherited from its colonial predecessor a political and administrative structure characterized by bureaucratic dominance which makes it very difficult for advocacy planning to flourish. A pioneer study was conducted of a sample of professional planners to investigate their role perceptions and performance, and their inclination to adopt advocacy planning. Results reveal that the respondents were ambivalent in their understanding and orientation to advocacy planning. Planners were largely confused about what constitutes the "public interest". Since they adopted a technocratic role perception and a conservative stance towards planning for social equity, they only recognized superficially the role of citizen participation, and had a rather negative perception of the ability of the territory's ascending political representatives to participate in planning. They were cautious about the prospects for advocacy planning in Hong Kong and were pessimistic concerning the post-1997 planning environment. - Reproduced
Keywords: Economic planning - Hong Kong; Economic planning